Koreografi Tari Piring Hoyak Badarai Di Sanggar Sarai Sarumpun Di Kota Padang - Tri Rafika Sari; Herlinda Mansyur (SENDRATASIK UNP, 2020)
This study aims to describe and explain the choreography of Piring Hoyak Badarai dance at Sarai Sarumpun Studio in Padang city. This is a qualitative research using descriptive method. The object of research was the Piring Hoyak Badarai dance. The instrument in this study was the researcher it self and was assisted by a voice recorder and several videos, a cell phone camera, and writing instruments. The data used were primary and secondary data. The data were got through collecting data, selecting important data, compiling data selected, and analyzing data using interpretation technique with careful consideration.  The results of this study indicate that Piring Hoyak Badarai dance is a creative dance originating from a traditional pattern movement which is developed into a creative dance shown as entertainment. In addition, this dance emerges from choreographed ideas, but it considers the norms and rules existing in the society. For instance, female dancers do not dance male dance movements because there are ethics in moving as well as ethics in dressing. The Piring Hoyak Badarai dance functions as an entertainment and develops the artistic potential of choreographers.  The Piring Hoyak Badarai dance with a theme manifested from traditional materials whose atmosphere is joyful has 33 kinds of movements and 5 dancers. The body lines contained in the Piring Hoyak Badarai dance are dominant to straight lines, the level is medium, the time is medium and fast, the upper design is angular,the floor pattern is straight and curved lines, andit is in the form of group dance developed by using dance composition knowledge by its choreographers.